Description Of Ankle Brachial Index In Persadia Community Who Undergo Diabetes Foot Gymnastics At Subang District Hospital - Julia Mulyani; Rosiah Rosiah; Minanton Minanton (Jurnal Ventilator, 2024)
Introduction: Diabetes mellitus is a degenerative disease with an increasing number of patients characterized by hyperglycemia due to impaired insulin secretion. Ineffective management in managing DM disease will result in complications such as peripheral artery disease (PAP). One of the examinations that can be done to find out the condition of the blood vessels of the lower extremities is by measuring the Ankle Brachial Index. One of the efforts to prevent the occurrence of PAP is by exercising diabetic feet. The purpose of this study is to analyze the picture of the Ankle Brachial Index in the Persadia Community who undergo diabetic foot exercises at Subang Hospital. Method: The method used in this study is quantitative descriptive. The sample in this study was 59 people taken using a simple random sampling technique. Data collection in this study used a sphygmomanometer and observation sheet, data analysis using frequency distribution. Results: The results of the study showed that the characteristics of respondents in the Persadia Community were 59 women (100.0%) with an average age of 50.03 years, IRT jobs as many as 28 people (47.5%) with the last high school education level of 35 people (59.3%). Meanwhile, the majority of ABI scores in the persadia community with an average score of 1.02. Conclusion: This study can be an input for DM patients to conduct routine ABI examinations to detect early vascular disorders in the extremities and as a prevention of the risk of leg ulcers.